Lipid Constituents of Diatoms (Halamphora) as Components for Production of Lipid Nanoparticles - Marta Marzec; Przemysław Dąbek; Andrzej Witkowski; Fernanda Monedeiro; Paweł Pomastowski; Bogusław Buszewski; Izabela Nowak (Pharmaceutics, 2022)
Lipid nanocarriers smaller than 200 nm may be used as pharmaceutical/cosmetic raw materials as they are able to penetrate the skin. The nanostructured lipid carriers (NLCs) based on microalgae oil (Schizochytrium) and lipids extracted from diatoms (Halamphora cf. salinicola (strain SZCZM1454A)) were produced by the HSH (high shear homogenization) method. Fatty acid profile of crude oil from diatoms indicated the presence of palmitoleic, palmitic, stearic acid, oleic and myristic acids as the most common fatty acids in the strain investigated. The quantitative composition and the synthesis condition of NLC dispersions were optimized by using the full factorial designs. The physicochemical parameters of the obtained lipid nanocarriers were characterized by SEM, DSC and XRD measurements and the fraction with the optimum parameters (size below 200 nm, polydispersity index not exceeding 0.2 and zeta potential higher than +45 mV) was selected for further study. The positive charge of the obtained lipid nanoparticles is beneficial as permits electrostatic bonding with the negatively charged skin surface. As follows from stability tests, the NLCs obtained could be stored at room temperature.